Sisimpur’s reach and educational impact: Evidence from a national longitudinal survey of a Sesame Street project in Bangladesh. - Lee, H.J. (Sesame Workshop, 2009)

Aid Effectiveness and Policy Ownership - Sobhan, R (Development and Change, 2002)

Bangladesh educational assessment: pre-primary and primary Madrasah education in Bangladesh - Abdalla, Amr; Raisuddin, A. N. M.; Hussein, Suieiman (Basic Education and Policy Support (BEPS) Activity, United States Agency for International Development, 2004)

The role of government and NGOs in slum development: the case of Dhaka City - Habib, Enamul (Development in Practice, 2009)
This article addresses the situation of slums in Dhaka City in relation to government and NGO mechanisms and priorities for slum development and upgrading. It concludes with specific suggestions for better slum management in the Bangladesh capital.

Quality of Education and Teacher Learning: A Review of the Literature - Leu, Elizabeth; Price-Rom, Alison (American Institutes for Research under the EQUIP1 LWA Academy for Educational Development, 2006)

Open and distance learning for basic education in South Asia: its potential for hard-to-reach children and children in conflict and disaster areas. - Morpeth, R; Creed, C; Cullen, J; Page, E; Raynor, J (United Nations Children's Fund, 2009)
Keywords: ___working_potential_duplicate

Dhaka: improving living conditions for the urban poor - World Bank (Bangladesh Development Series, 2007)